2019
DOI: 10.1182/bloodadvances.2018026955
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironment and clonal monocytes from chronic myelomonocytic leukemia induce a procoagulant climate

Abstract: Chronic myelomonocytic leukemia (CMML) is a myeloid hematological malignancy with overlapping features of myelodysplastic syndromes (MDSs) and myeloproliferative neoplasms (MPNs). The knowledge of the role of the tumor microenvironment (TME), particularly mesenchymal stromal cells (MSCs), in MDS pathogenesis is increasing. Generally, cancer is associated with a procoagulant state participating in tumor development. Monocytes release procoagulant, tissue factor (TF)–bearing microparticles. We hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…CMML has generally been exclusively considered as an HSPC events‐driven disease over the past decades. Recently, accumulating evidence has indicated that functional alterations in BM MSCs contribute to the development of myeloid malignancies 4,31,32 . Raaijmakers et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMML has generally been exclusively considered as an HSPC events‐driven disease over the past decades. Recently, accumulating evidence has indicated that functional alterations in BM MSCs contribute to the development of myeloid malignancies 4,31,32 . Raaijmakers et al .…”
Section: Discussionmentioning
confidence: 99%
“…2 Recent experimental data have emphasized the participation of bone marrow mesenchymal elements in the pathogenesis of multiple myeloid malignancies, while studies on the bone marrow microenvironment in CMML are rare. 3,4 Generally, genetic perturbations of mesenchymal cells are sufficient to induce MDS/acute myeloid leukaemia (AML)-like phenotypes, which establish a concept of 'niche-induced' oncogenesis. 5,6 These studies challenged the concept that myeloid disorders are exclusively driven by autonomous events in haematopoietic cells.…”
Section: Chronic Myelomonocytic Leukaemia (Cmml) Is a Myeloid Malignancy With Features Overlapping With Myelodysplastic Syndromes (Mds) Amentioning
confidence: 99%
“…Chronic myelomonocytic leukemia (CMML) is a myeloid hematological malignancy with overlapping characteristics of MDS and MPN. It has been reported that CMML monocyte EVs confer a procoagulant activity to healthy donor MSC, which can be reversed by an anti-TF antibody [ 136 ].…”
Section: Ev Functions Related To the Hypercoagulable State Of Bloomentioning
confidence: 99%
“…In chronic myeloid leukemia (CML), leukemia cells altered the cellular and immune-related properties of BM-MSCs and macrophages in vitro by the mean of exosomes ( Jafarzadeh et al, 2019 ). Consistently, Zannoni et al (2019) reported that EVs released by monocytes from chronic myelomonocytic leukemia patients conferred a procoagulant state favorable for cancer progression, through a tissue factor-dependent mechanism mediated by MSCs. In glioma, exosomes from cancer cells induced a tumor-like phenotype in MSCs by activating glycolysis ( Ma et al, 2019 ).…”
Section: Evidence Of Stromal Cell Programming By Tumor Microenvironmementioning
confidence: 64%